Pole and Hungarian Cousins Be? A Comparison of State Media Capture, Ideological Narratives and Political Truth Monopolization in Hungary and Poland - Aron Kerpel-Fronius (Slovo, 2017)
Pole and Hungarian Cousins Be? A Comparison of State Media Capture, Ideological Narratives and Political Truth Monopolization in Hungary and Poland